Non-Canonical G-quadruplexes cause the hCEB1 minisatellite instability in Saccharomyces cerevisiae - Piazza, Aurèle (2017)
G-quadruplexes (G4) are polymorphic four-stranded structures formed by certain G-rich nucleic acids in vitro, but the sequence and structural features dictating their formation and function in vivo remains uncertain. Here we report a structure-function analysis of the complex hCEB1 G4-forming sequence. We isolated four G4 conformations in vitro, all of which bear unusual structural features: Form 1 bears a V-shaped loop and a snapback guanine; Form 2 contains a terminal G-triad; Form 3 bears a zero-nucleotide loop; and Form 4 is a zero-nucleotide loop monomer or an interlocked dimer. In vivo, Form 1 and Form 2 differently account for 2/3rd of the genomic instability of hCEB1 in two G4-stabilizing conditions. Form 3 and an unidentified form contribute to the remaining instability, while Form 4 has no detectable effect. This work underscores the structural polymorphisms originated from a single highly G-rich sequence and demonstrates the existence of non-canonical G4s in cells, thus broadening the definition of G4-forming sequences.